2018
DOI: 10.1200/jgo.18.00088
|View full text |Cite
|
Sign up to set email alerts
|

Patient Factors Associated With Delays in Obtaining Cancer Care in Botswana

Abstract: PurposeDelays in diagnosis and treatment of cancers can lead to poor survival. These delays represent a multifaceted problem attributable to patient, provider, and systemic factors. We aim to quantify intervals from symptom onset to treatment start among patients with cancer in Botswana and to understand potential risk factors for delay.Patients and MethodsFrom December 2015 to January 2017, we surveyed patients seen in an oncology clinic in Botswana. We calculated proportions of patients who experienced delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 38 publications
3
42
0
3
Order By: Relevance
“…Including it will reduce financial burden and delays due to lack of finance for those covered by the scheme. For the majority not covered by the scheme, a kind of government subsidy or government bearing the cost of radiotherapy as is practiced in Botswana may be an appropriate strategy [ 30 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Including it will reduce financial burden and delays due to lack of finance for those covered by the scheme. For the majority not covered by the scheme, a kind of government subsidy or government bearing the cost of radiotherapy as is practiced in Botswana may be an appropriate strategy [ 30 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Men and women with no education had higher overall cancer incidence rates compared to the educated population. [5][6][7][8] Here, in this study 81.6% of patients presenting in late stage are illiterate which may indirectly indicate the lack of knowledge about cancer in this subset. Patient's socioeconomic characteristics are predictors of patient, doctor and system related delay in cancer diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Where gender differences existed, female subjects had longer delays than male subjects. 6,9 House hold works and more domestic responsibilities in Indian women contribute towards their negligence for availing health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the research conducted, it was found that men were more likely to be late in seeking a diagnosis of cancer symptoms and late in treating cancer compared to women. This is because men are more masculine, so they tend to be less likely to seek help and less exposed to the health system [9], [10]. While women more often utilise health services related to pregnancy and role [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to research conducted by the type of cancer that often experiences delays is a type of cancer experienced by men compared to the type of cancer associated with women. This relates to women, in general, tend to act as role models for other people living with cancer and are more often exposed to health services [10].…”
Section: Discussionmentioning
confidence: 99%